Covid-19 Prediction Model (COVID-19-PM) For Social Distancing: The Height Perspective: COVID-19 Prediction Model for Social Distancing: The Height Perspective - Okwonu, Friday Zinzendoff; Ahad, Nor Aishah; Apanapudor, Joshua Sarduana; Arunaye, Festus Irimisose (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The outbreak of the coronavirus in Wuhan city, China in December 2019 has taken a different dimension that the World Health Organization declared it PANDEMIC in January 2020. The virus was later code named Covid-19.Covid-19 is now a global concern ravaging the world. Different suggestions on possibilities to control the spread of the virus have been advanced in recent times. Nonpharmaceutical approaches such as partial lockdown, total lockdown,and social distancing have been adopted to reduce the spread of the Covid-19. This study focused on how effective social distancing is to curtail the spread of Covid-19. The objective of this study is to determine the social distancing value measured in meters that could help reduce the spread of the virus. In this study, we proposed a prediction model based on social distancing value and height to investigate whether social distancing will help curtail the spread of the virus. The model is classified as detection and prediction phases. The prediction phase utilizes information from the detection phase to analyse the effect of social distancing value on the spread of Covid-19. The study revealed that as the social distancing value increases, the probability of spread decreases. The result also showed that as the social distancing values increases, the probability of safety from been infected increases. The study concludes that increasing the social distancing value up to three or four meters could reduce the probability of spread and increase the probability of safety from been infected by the virus.